Mapping Benthic Habitat Distribution and Coral Reef Health Index in Ternate Island and Tidore Island, North Maluku - Patty, Simon I.; Souhoka, Jemmy; Makatipu, Petrus C.; Rizqi, Marenda Pandu (Sam Ratulangi University, 2024)
Coral reefs are underwater marine organisms whose coverage can be identified using remote sensing technology utilizing satellite imagery. The benthic habitats classification and coral reef health index analysis were carried out on the Ternate and Tidore islands in June 2021. This study aims to map the distribution of benthic habitat as well as calculate the value of the coral reef health index. The processing of satellite imagery data from Landsat 8, using ENVI 5.3 and ArcGIS 10.1 software. The